Effect of nutritive and nonnutritive sweeteners on the quality of biscuits - El-Sayed, Sally S.; Agamy, Neveen F. (2013)
Biscuits were prepared by replacing sucrose with dietetic sweeteners fructose, sorbitol, mannitol and stevia. Physical studies of biscuits revealed that replacement of sucrose with mannitol decreased greatly the width from 5.10 cm to reach 4.95 cm. The thickness was increased from 0.40 cm in Tb1 (B(sucrose) to 0.48 cm in Tb5 (B(sorbitol). Maximum spread factor (13.15 cm) was obtained in Tb1 (B(sucrose), while the lowest spread factor was 9.71 cm in Tb5 (B(sorbitol). Sensory evaluation of the biscuits was evaluated at different time of storage (30, 60 and 90 days) to find the best treatment for commercialization. The results pertaining to sensory evaluation of biscuits indicated that the color, odor, texture and after taste gave the best score in Tb1 (B(sucrose) at 0 days and the taste have its high score after 30 days of storage, while the worst score of taste, odor and texture was in Tb2 (B(fructose) after 90 and 30 days of storage. The worst score in color and after taste was in Tb4 (B(mannitol) and Tb3 (B(stevia), respectively after 60 and 90 days of storage.s
Includes references.
Summary in Arabic.
1
Keywords: Biscuits -- Quality; Sweeteners; Nonnutritive sweeteners